The Influence Of Good Corporate Governance And Intellectual Capital On Financial Performance (Empirical Study Of Banking Companies Listed On The BEI In 2018 - 2022) - Kusnandar, Dadan; Holiawati, Holiawati; Nofryanti, Nofryanti (Indonesian Development of Economics and Administration Journal, 2024)
Purpose – This study evaluates the impact of Good Corporate Governance (GCG) and Intellectual Capital on the financial performance of banks in Indonesia during the period 2018-2022. The background of this research is the importance of the banking sector to the Indonesian economy and the challenges it faces due to global economic instability and the Covid-19 pandemic. Methodology/approach – The research method uses secondary data from the financial reports of banks listed on the Indonesia Stock Exchange (IDX). Findings – Testing was conducted using a panel data regression model, and the results show that GCG has a significantly negative impact on financial performance, while Intellectual Capital has a significantly positive impact. Novelty/value – The novelty in this research lies in the research object used, namely the financial sector listed on the IDX for the period 2018-2022.